PENGEMBANGAN KARAKTER ANAK USIA DINI MELALUI SIMULASI KECAKAPAN HIDUP - Widayati, Tri (JIV-Jurnal Ilmiah Visi, 2013)
The purposes of this research were do describe the process of character building through life skill simulation and to develop the children’s character through life skill simulation. This action research was conducted in three early childhood education institutions for six months started from March through July 2013. The researcher did the research in collaboration with the local teachers to assess, plan, implement, observe, and do reflection. T test indicated a significant difference between the character development degree before and after the simulation. The hindrances in developing the character through life skill simulation are the children’s shy feeling and low self-confidence as well as the teachers’ limitation in designing the simple, interesting, and easy simulation scenario.